Air bubbles removal technique from intravenous tubing - Irwanto, Andre; Santosa, Agus (Universitas Muhammadiyah Purwokerto, 2022)
Background: The air bubbles in the intravenous tubing can be fatal if it enters the body. It can result in an air embolism. Air embolism is a condition in which air bubbles enter the blood vessels. Several methods can be used to remove air bubbles in the intravenous tubing. One is replacing it with new intravenous tubing, but this method is considered less efficient. This article describes effective and efficient ways to remove air bubbles from intravenous tubing and tests them for effectiveness.Technique: Four techniques can be applied when the intravenous tubing is filled with air, namely the roll-up technique, flick technique, combination roll-up and flick technique, and push-pull technique.Conclusion: From the test, the push-pull technique is the most effective and efficient in removing air from intravenous tubing compared to the others.